2008
DOI: 10.1111/j.1539-6924.2008.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Trust in the Safety of Tourist Destinations: Hard to Gain, Easy to Lose? New Insights on the Asymmetry Principle

Abstract: According to the asymmetry principle of trust, negative events decrease trust to a much higher extent than positive events increase trust. The study at hand intended to verify whether this notion of asymmetry holds true with respect to trust in the safety of tourist destinations. Thus, in contrast to previous research that analyzed trust asymmetry in the context of involuntary technological risks, the present study evaluates the validity of the asymmetry principle of trust in the context of voluntary tourism r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(67 reference statements)
1
16
0
2
Order By: Relevance
“…( 93,94 ) As for types of hazards, White and Eiser contrasted a high‐risk hazard to a low‐risk hazard, ( 92 ) and Eitzinger and Wiedemann compared involuntary with voluntary hazards. ( 95 ) In each of these distinctions, one element is taken to be susceptible to trust asymmetry (events, performance, abilities; high‐risk, voluntary), while the other is resistant to it (policies, morality, intentions; low‐risk, voluntary). The consensus model of trust does not accommodate types of hazards as moderators; their effects are simply empirical matters.…”
Section: Discussionmentioning
confidence: 99%
“…( 93,94 ) As for types of hazards, White and Eiser contrasted a high‐risk hazard to a low‐risk hazard, ( 92 ) and Eitzinger and Wiedemann compared involuntary with voluntary hazards. ( 95 ) In each of these distinctions, one element is taken to be susceptible to trust asymmetry (events, performance, abilities; high‐risk, voluntary), while the other is resistant to it (policies, morality, intentions; low‐risk, voluntary). The consensus model of trust does not accommodate types of hazards as moderators; their effects are simply empirical matters.…”
Section: Discussionmentioning
confidence: 99%
“…As Eitzinger and Wiedemann (2008) found, contexts of voluntary exposure to risk are not well explained by theories of trust developed in non-voluntary 196 P. Lynch and M. Dibben…”
Section: Discussionmentioning
confidence: 71%
“…Neither these studies nor those focusing on smallerscale events (Reid and Ritchie 2011;Soderman and Dolles 2013) address trust as an aspect of risk management. However, one recent study from the tourism literature (Eitzinger and Wiedemann 2008) investigated patterns of trust in the safety management of alpine tourist destinations, finding that in the context of 'voluntary and at least partly controllable risks' (851), trust processes diverge from the main body of trust theory. Contrary to research on trust in the context of involuntary exposure to risk, Eitzinger and Wiedemann found that:…”
Section: Trust In Leisure and Adventure Contextsmentioning
confidence: 99%
“…Establishing and maintaining public trust is considered an important constituent of successful risk management. ( 1,2 ) As a result, there has been considerable debate about aspects of risk managers ( 3‐9 ) and of risk management events ( 10‐15 ) upon which citizens base their trust judgments. The recently developed intuitive detection theorist (IDT) model addresses both issues.…”
Section: Introductionmentioning
confidence: 99%